Tacrolimus trough monitoring guided by mass spectrometry without accounting for assay differences is associated with acute kidney injury in lung transplant recipients. (7th November 2019) - Kolaitis, Nicholas A; Calabrese, Daniel R; Ahearn, Patrick; Venado, Aida; Florez, Rebecca; Lei, Huey-Ling; Isaak, Karolina; Henricksen, Erik; Martinez, Emily; Chong, Tiffany; Shah, Rupal J; Leard, Lorriana E; et al.
Abstract: Purpose: Tacrolimus is a nephrotoxic immunosuppressant historically monitored via enzyme-based immunoassay (IA). After 2011, the 2 largest laboratory companies in the United States implemented tacrolimus quantification by liquid chromatography–mass spectrometry (LC-MS); this method excludes metabolites, potentially resulting in lower quantified drug concentrations. We sought to determine if tacrolimus therapeutic drug monitoring via LC-MS, as performed using trough targets originally derived from IA values, influences clinical outcomes. Methods: In a single-center retrospective cohort study of lung transplant recipients, risks of acute kidney injury, acute renal failure, and new-onset diabetes after transplantation, as well as chronic lung allograft dysfunction–free survival, were compared in 82 subjects monitored by LC-MS and 102 subjects monitored by IA using Cox proportional hazard models adjusted for age, sex, baseline renal function, and race. Results: LC-MS–based monitoring was associated with a greater risk of acute kidney injury (adjusted hazard ratio, 1.65; 95% confidence interval, 1.02–2.67). No statistically significant differences in risks of acute renal failure and new-onset diabetes after transplantation were observed. Conclusion: Although LC-MS provides a more accurate representation of the blood concentration of the parent compound tacrolimus exclusive of metabolite, established cut points for tacrolimus dosing may need to be adjusted to account for the increased risk of renal injury.